2014
DOI: 10.1007/978-1-4939-1372-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Changes Induced by Prenatal Stress in Behavior and Brain Morphology: Can They Be Prevented or Reversed?

Abstract: This chapter presents a critical analysis of the behavioral alterations reported in the offspring of women exposed to stress and/or depression during pregnancy and the neurochemical and structural changes underlying them. Among the alterations attributed to prenatal stress in humans and experimental rats of both sexes is impaired regulation of the hypothalamic-pituitary-adrenal (HPA) axis, anxiety and exaggerated fear of novelty, and decreased social interaction. Learning and attention deficits are more preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 139 publications
1
23
2
1
Order By: Relevance
“…These results suggest CF-induced changes in metabotropic glutamate signaling and NE signaling could be partially restoring the balance in excitatory and inhibitory transmission within the amygdala of PS offspring, thus ameliorating anxiogenic behaviors observed. Previous studies manipulating quality of maternal care by neonatal handling have shown the reversal of both anxiogenic behavior and HPA axis hyperactivity following PS (Maccari et al, 1995;Vallée et al, 1997;Weinstock, 2015). In our study, cross-fostering was not effective in rescuing the enhanced HPA axis drive and increased state of vigilance noted in PS offspring, suggesting the influence of psychosocial PS on these phenotypes differs from the effect of other types of prenatal insults, with psychosocial PS being associated with more persistent deleterious alterations.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…These results suggest CF-induced changes in metabotropic glutamate signaling and NE signaling could be partially restoring the balance in excitatory and inhibitory transmission within the amygdala of PS offspring, thus ameliorating anxiogenic behaviors observed. Previous studies manipulating quality of maternal care by neonatal handling have shown the reversal of both anxiogenic behavior and HPA axis hyperactivity following PS (Maccari et al, 1995;Vallée et al, 1997;Weinstock, 2015). In our study, cross-fostering was not effective in rescuing the enhanced HPA axis drive and increased state of vigilance noted in PS offspring, suggesting the influence of psychosocial PS on these phenotypes differs from the effect of other types of prenatal insults, with psychosocial PS being associated with more persistent deleterious alterations.…”
Section: Discussioncontrasting
confidence: 76%
“…However, the contributing mechanisms by which these intrauterine challenges program disease susceptibility remain largely unknown. Studies in rodents have demonstrated that PS can result in the emergence of anxiety-like and depressiverelated behaviors, reduced social interaction, and deficits in attention and learning (Brunton, 2013;Weinstock, 2015). These phenotypes are often accompanied by dysregulation in hypothalamic-pituitary-adrenal (HPA) axis activity (Glover et al, 2010), the main neuroendocrine system regulating responses to stress, and such dysregulation is a common feature in humans suffering from depression and anxiety disorders (Young, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal stress can induce long-term neurodevelopmental diseases, particular those related to the hypothalamic-pituitary-adrenal (HPA) response to stress51. This exposure to maternal stress may alter the stress-vulnerability of the embryo leading to an increased risk of psychopathology36.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to respond appropriately to stress is a crucial determinant in later vulnerability to neuropsychiatric disorders (Nestler et al, 2002). Indeed, epidemiological, clinical, and basic animal studies have shown that both PAE and PS increase the risk of adverse neurodevelopmental outcomes including HPA hyperresponsiveness and vulnerability to mental health disorders (Maccari and Morley-Fletcher, 2007; Hellemans et al, 2010; Weinstock, 2015). These adverse outcomes may be due, at least partly, to increased fetoplacental glucocorticoid (cortisol in human; corticosterone [CORT] in rats) exposure, as studies in animal models have shown that PAE and PS both increase maternal plasma CORT levels (Weinberg and Bezio, 1987; Maccari et al, 2003), which could, in turn, impact the fetus.…”
Section: Introductionmentioning
confidence: 99%